The Complexities of Navigating the Healthcare System as an Autistic Individual with Ehlers-Danlos Syndrome: A Patient Perspective - Sarah Clark (Journal of Patient Experience)
Autistic individuals with hypermobile Ehlers-Danlos syndrome (hEDS) often face unique challenges navigating healthcare systems due to lack of clinician awareness, diagnostic delays, misdiagnoses, and systemic barriers. Drawing on my own lived experience within the UK's National Health Service (NHS), this patient perspective article integrates personal narratives with the research and literature, highlighting critical gaps in clinical care, offering practical recommendations to enhance equity and inclusion. Recommendations include: improved clinician education on neurodivergence and overlapping conditions, improving holistic patient-centred communication, and collaborative care models that prioritise patient needs, learning from lived expertise.